Applications of the Atmospheric Transport and Diffusion of LES Modeling to the Spread and Dissipation of COVID-19 Aerosol Particles inside and outside the Japan National Stadium (Tokyo Olympic Stadium). (9th June 2021) - Uchida, Takanori; Araya, Ryo
Abstract : In this paper, we use an analysis function for gas diffusion known as the Research Institute for Applied Mechanics, Kyushu University, Computational Prediction of Airflow over Complex Terrain (RIAM-COMPACT), which was developed for complex terrain, in Airflow Analyst software, and apply it to the spread and dissipation of a fluid layer (assuming the fluid layer contains COVID-19 particles). First, to verify the prediction accuracy of the gas diffusion using RIAM-COMPACT, comparisons with past wind tunnel test results conducted on simple and complex terrains are presented under neutral atmospheric stability. The results of the numerical simulations carried out in this study show good agreement with the wind tunnel experiments for both simple and complex terrains. Next, a model of the Japan National Stadium (Tokyo Olympic Stadium) was constructed using 3D detailed topographic Advanced World 3D Map (AW3D) data generated by combining high-resolution satellite images. We tried to reproduce the hypothetical spread and dissipation of the fluid layer (assuming the fluid layer contains COVID-19 particles) inside and outside of the Japan National Stadium using Airflow Analyst implemented with the RIAM-COMPACT analysis function for gas diffusion. We paid special attention to the effect of wind ventilation driven by natural wind. The numerical results under various scenarios show that ventilation driven by natural wind is very effective for the Japan National Stadium.